Role-Based Access Control in Cybershield Cloud: Safeguarding Industry 4.0 Applications - Sivananda Reddy Julakanti (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The advent of Industry 4.0 has revolutionized industrial operations through the integration of the Industrial Internet of Things (IIoT), enabling unprecedented levels of data collection, analysis, and automation. Central to these advancements is cloud computing, which offers scalable storage and processing capabilities essential for managing the vast and continuous data streams generated by IIoT devices. However, the security and privacy of this data remain paramount concerns, as the potential for data breaches and unauthorized access poses significant risks to industrial operations. This paper introduces CyberShield Cloud, a robust data storage and sharing system designed to secure Industry 4.0 applications through Role-Based Access Control (RBAC) and advanced encryption techniques. CyberShield Cloud employs a novel symmetric homomorphic encryption scheme that not only ensures data confidentiality but also supports analytics on encrypted time-series data without compromising security. The system facilitates fine-grained access control, allowing data owners to define specific access permissions based on user roles and temporal requirements. Comprehensive simulations demonstrate that CyberShield Cloud achieves a 17% reduction in query time and a 9% improvement in throughput compared to existing benchmark schemes. These results underscore the system’s efficacy in enhancing data security while maintaining high performance in IIoT environments. CyberShield Cloud represents a significant step forward in safeguarding industrial data, ensuring both security and operational efficiency in the era of smart manufacturing.